EVALUASI DOSIS FOTON PADA PASIEN KANKER REKTUM DENGAN TEKNIK 3DCRT DAN IMRT - Novinda, Gabriella; Illya, Gregoria (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2024)
Rectal cancer is one of the deadliest cancers in Indonesia. Treatment of rectal cancer is often done with radiotherapy. External radiotherapy of rectal cancer uses linac which has several methods of irradiation. This study aims to determine the distribution of photon doses through the Conformity Index (CI) and Homogeneity Index (HI) values as well as the doses received by healthy tissue around cancer tissue. This study also aims to find out better methods of external radiotherapy. Making treatment planning using Xi-O TPS software. This study on the 3DCRT method produced HI values of 0.084 ± 0.017 and CI values of 0.98 ± 0.02. In the IMRT method, the HI value is 0.099 ± 0.028 and the CI value is 0.96 ± 0.03. Based on HI and CI analysis, it was found that the 3DCRT method was better than IMRT in the treatment of rectal cancer but not significantly. Meanwhile, the IMRT bowel bag method has a lower average dose compared to the 3DCRT method and the results are significant. In bladder and femoral tissues, the IMRT method is better than the 3DCRT method but is not significant. In rectal cancer, the IMRT technique is better because it can minimize the dose of OAR.